Income taxes and the composition of pay - Giorgio Brunello; Simona Comi; Daniela Sonedda (Institute for the Study of Labor (IZA), 2006)
According to the standard principal-agent model, the optimal composition of pay should balance the provision of incentives with the individual demand for insurance. Do income taxes alter this balance? We show that the relative share of PRP on total pay is reduced by higher average taxes, and is affected in a complex way by higher marginal tax rates. Empirical evidence based on the British Household Panel Survey, which exploits the UK 1999 Tax Reform, supports the theoretical predictions of the tax-augmented principal-agent model.
Keywords: J33; H24; 330; performance related pay; income taxes